New insights and advances of sodium-glucose cotransporter 2 inhibitors in heart failure - Li, Juexing; Zhou, Lei; Gong, Hui (Frontiers in Cardiovascular Medicine, 2022)
Sodium-glucose cotransporter 2 inhibitors (SGLT2i) is an emerging non-insulin-dependent oral hypoglycemic agent which works independently of β-cells. Quite a few large-scale clinical trials have demonstrated the cardiovascular protective function of SGLT2i, and no matter patients with diabetes or not could benefit from those agents. By searching all relevant keywords related to our topics over past 3 years including all the names of agents and their brands in PubMed, here we review the mechanisms underlying the improvement of heart failure. We also discuss the interaction of mechanisms from different pieces of literature including corresponding and contradict opinions to support each subtopic. Several potential mechanisms of SGLT2i contributing to heart failure improvement have been discussed in this manuscript including the regulation of diuresis, the excretion of sodium, the shedding of pounds, the improvement of blood pressure control, the stimulation of hematocrit and erythropoietin, the remolding of metabolism, the prevention from structural dysregulation, etc. Although some are controversial or even contradictory, those newly emerging agents hold great promise for the future in cardiology-related therapy, and more research acquired to be conducted to confirm their function, especially in the field of metabolism, Na+-H+ exchange protein, and myeloid angiogenic cells.